An Investigation on Mechanical Behavior of Tooth-Plate-Glass-Fiber Hybrid Sandwich Beams. (12th February 2020) - Xie, Honglei; Wan, Li; Wang, Bo; Pei, Haiping; Liu, Weiqing; Yue, Kong; Wang, Lu
Abstract : Tooth-plate-glass-fiber hybrid sandwich (TFS) is a type of sandwich composites fabricated by vacuum-assisted resin infusion process, in which glass fiber facesheets reinforced by metal plate are connected to foam core through tooth nails. Bending properties and interlaminar properties of TFS beams with various foam densities were investigated by flexural tests and DCB (double cantilever beam) tests. The test results showed that by increasing the foam core density from 35 kg/m 3 to 150 kg/m 3, the peak strength of TFS beams significantly increased by 168% to 258% compared with similar sandwich beams with fibrous composite facesheets. With the change of foam density and span length, the main failure modes are core shear and facesheet indentation beneath the loading roller. The interlaminar strain energy release rates of TFS specimens also increased by increasing the density of the foam. In addition, an analytical model was used to predict the ultimate bending strength of TFS beams, which were in good accordance with the experimental results.